Sustainable careers of self-initiated expatriates - Lindgren, Sonja (My University, 2025)
The concept of a career has evolved significantly over time and maintaining a single long-term employment relationship throughout one’s working life has become increasingly uncommon. Sustainable careers have gained greater recognition in recent years as a framework for understanding how individuals can build long-lasting careers in a complex and unpredictable labor market. However, the sustainable careers of self-initiated expatriates (SIEs) have not been studied extensively, despite their unique, global career trajectories that differ substantially from those who build their careers in their home country. SIEs offer an important perspective on sustainable careers because they are driven by strong personal agency, experience multiple contextual influences and face new distinct challenges. The lack of prior studies in the area reveals a significant gap in the literature, which this thesis seeks to address. This study explores how career sustainability is shaped by self-initiated expatriation and, using the sustainable career theory, examines the influence of personal, contextual, and time factors on SIEs' careers. This study was conducted as qualitative research using semi-structured interviews to collect data from self-initiated expatriates who had undergone one or more expatriations. In total, nine participants were interviewed, focusing on their past, present and future experiences and goals. The analysis was done based on the indicators (health, happiness and productivity) and dimensions (person, context and time) of sustainable career theory. The findings suggest that the experiences of self-initiated expatriates provide valuable insights into sustainable careers by illustrating how they actively manage their careers through personal resilience, adaptability and meaningful career motivations, which contribute to their health, happiness, and productivity over time. Career sustainability among SIEs was positively influenced by the expatriation experience, as many participants expressed gratitude for the challenges they encountered, reporting that these experiences strengthened their careers. Managing the time sequences of changing contexts helped the SIEs establish meaningful and satisfying careers that aligned with their personal needs and skill set. Overall, the study deepens the theoretical and practical understanding of sustainable careers in the context of self-initiated expatriation. Additionally, this study provides suggestions for further research based on limitations this research had as well as suggesting further perspectives to study more to gain an even deeper understanding of the phenomenon.

Ura-käsitys on muuttunut merkittävästi ajan myötä ja yhden pitkäaikaisen työsuhteen ylläpitäminen koko työuran ajan on nykyään yhä harvinaisempaa. Kestävät urat ovat viime vuosina saaneet kasvavaa tunnustusta viitekehyksenä, jonka avulla voidaan ymmärtää, miten yksilöt voivat rakentaa pitkäkestoisia uria monimutkaisilla ja ennakoimattomilla työmarkkinoilla. Oma-aloitteisten ekspatriaattien kestävien urien tutkimusta ei kuitenkaan ole tehty laajasti, vaikka heidän ainutlaatuiset, globaalit urapolkunsa eroavat merkittävästi niistä, jotka rakentavat uransa kotimaassaan. Oma-aloitteiset ekspatriaatit tarjoavat tärkeän näkökulman kestävien urien tarkasteluun, sillä heitä ohjaa vahva henkilökohtainen toimijuus, he kokevat erilaisia kontekstuaalisia vaikutuksia ja kohtaavat uudenlaisia haasteita. Aihetta koskevan tutkimuksen puute osoittaa merkittävän aukon kirjallisuudessa, jota tämä tutkimus pyrkii osittain täyttämään. Tutkimuksen tavoitteena on selvittää, miten oma-aloitteinen ekspatriaattisuus vaikuttaa uran kestävyyteen ja miten henkilökohtaiset, kontekstuaaliset ja ajalliset tekijät muokkaavat oma-aloitteisten ekspatriaattien urakehitystä käyttäen kestävän uran teoriaa viitekehyksenä. Tutkimus toteutettiin kvalitatiivisena tutkimuksena käyttäen puolistrukturoituja haastatteluja, joissa kerättiin tietoa oma-aloitteisilta ekspatriaateilta, jotka olivat kokeneet yhden tai useamman ulkomaanjakson. Haastatteluissa keskityttiin osallistujien menneisiin, nykyisiin ja tuleviin urakokemuksiin ja tavoitteisiin. Analyysi tehtiin kestävän uran teorian indikaattoreiden (terveys, onnellisuus ja tuottavuus) ja ulottuvuuksien (henkilö, konteksti ja aika) pohjalta. Tulokset osoittavat, että oma-aloitteisten ekspatriaattien kokemukset tarjoavat arvokasta tietoa kestävistä urista havainnollistamalla, miten he aktiivisesti hallitsevat uraansa henkilö-kohtaisen joustavuuden, sopeutumiskyvyn ja merkityksellisten uramotivaatioiden avulla, mikä tukee heidän terveyttään, onnellisuuttaan ja tuottavuuttaan ajan myötä. Oma-aloitteisien ekspatriaattien uran kestävyys vahvistui usein ulkomaanjaksojen kautta koettujen haasteiden ansiosta. Muuttuvien kontekstien ajallinen hallinta auttoi oma-aloitteisia ekspatriaatteja rakentamaan merkityksellisiä ja tyydyttäviä uria, jotka vastasivat heidän henkilökohtaisia tarpeitaan ja osaamistaan. Yleisesti, tämä tutkimus syventää kestävien urien teoreettista ja käytännön ymmärrystä oma-aloitteisen ekspatriaattisuuden kontekstissa. Lisäksi tutkimus tarjoaa ehdotuksia jatkotutki-mukselle tutkimuksen rajoitusten pohjalta ja ehdottaa näkökulmia, joiden avulla ilmiötä voidaan tarkastella entistä syvällisemmin.
Keywords: expatriates; health; happiness; productivity; context; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business